TANGGUNG JAWAB NEGARA DALAM PENGELOLAANSUMBER DAYA AIR - Adisa Maulita, Mrs. (Jurnal Ilmiah Administrasi Publik, 2012)
This research was conducted based on thinking that today in Indonesiais facing various problems. The breakingdown of water is often related with blunderof life environmental management,changing of land management, domesticand industry pollution and also overexploitation of water resource, pressing ofpopulation growth and economic activity.Those aspects cause the disturbanceirrigation distribution to field area. Big andlittle water debit streaming to the field isdepending on dam situation. Depending ofmain water supply has very important roleto food sector. Objective of this research is toanalyze state responsibelity in waterresource management in water resourcemanagement at Perum Jasa Tirta I withsuccesfull of Perum Jasa Tirta I inimplementing state responsibelity in waterresource management itself.This research is using descriptive qualitative method. All data were obtainedfrom interview result, observation andtechnical documentation. Data analysisused in this research is interactive dataanalysis model according to Miles andHuberman. Result of this research showed thatwater resources management managedby Perum Jasa Tirta I, Malang Town hasbeen suitable with Act Number 7, 2004 asfoundation of water resource managementin Indonesia.Water resource managementincludes 3 elements: conservation, usingand controlling of water disturbancepower. The third elements have beengood enough conducted and implementedby Perum Jasa Tirta I as implementer ofwater resource manager at WA DASBrantas and Bengawan Solo. Supporting aspects for increasingresponsibility in water resourcemanagement is: information system (waterresource information, facilities of waterresource information, and managementinstitution); empowerment and people role;SDA Board; Water Resource ManagementPattern, and Water ResourceManagement Plan; the exisiting ofincreasing people participation and farmerin developing positive social control,competent human resource, increasing ofinstitution coordination involved in waterresource management, increasing controlfor operation & maintenance.